Experimental film and queer materiality - Suárez, Juan Antonio 1972- (Oxford University Press, 2024)
"This book shows that experimental cinema revealed a peculiar latency of the modern everyday that can be called queer materiality. Queer materiality designates a sense of queer possibility in modern material culture, which often inspired queer artists and filmmakers to envision wayward bodies and behaviors; it also refers to the way in which sexual and social dissidence was embedded in the objects, technologies, substances, and spaces that make up the hardware of experience. Experimental film offers a rich archive of queer material engagements. This book studies various queer material configurations in the work of well-known filmmakers such as Andy Warhol, Barbara Hammer, Carolee Schneemann, or Jack Smith, but it also explores under-recognized figures such as Tom Chomont, Jim Hubbard, Ashley Hans Scheirl or Teo Hernández. Combining history, formal analysis, and theoretical reflection, the book shows how plastics, glitter, mechanical ensembles, urban ruins, garbage, mood-enhancers such as amphetamine, film grain, or noise have been mobilized in the articulation of queerness for the screen. The book's inquiry into the liveliness of matter and into the interface between sexuality and the material world directly resonates with a growing ecological consciousness and with current concerns about the definition and reach of the human in a universe of intricate post-human entanglements"--
Keywords: Geschichte 1945-1985; Experimentalfilm; LGBT -- Motiv; USA; Experimental film / History; Sexual minorities in motion pictures; Minorités sexuelles au cinéma